Digital Magnetic Sorting for Fractionating Cell Populations with Variable Antigen Expression in Cell Therapy Process Development - Savannah Bshara-Corson; Andrew Burwell; Timothy Tiemann; Coleman Murray (Magnetochemistry)
Cellular therapies exhibit immense potential in treating complex diseases with sustained responses. The manufacture of cell therapies involves the purification and engineering of specific cells from a donor or patient to achieve a therapeutic response upon injection. Magnetic cell sorting targeting the presence or absence of surface markers is commonly used for upfront purification. However, emerging research shows that optimal therapeutic phenotypes are characterized not only by the presence or absence of specific antigens but also by antigen density. Unfortunately, current cell purification tools like magnetic or fluorescence-activated cell sorting (FACS) lack the resolution to differentiate populations based on antigen density while maintaining scalability. Utilizing a technique known as digital magnetic sorting (DMS), we demonstrate proof of concept for a scalable, magnetic-based approach to fractionate cell populations based on antigen density level. Targeting CD4 on human leukocytes, DMS demonstrated fractionation into CD4Hi T cells and CD4Low monocytes and neutrophils as quantified by flow cytometry and single-cell RNA seq. DMS also demonstrated high throughput processing at throughputs 3–10× faster than FACS. We believe DMS can be leveraged and scaled to enable antigen density-based sorting in cell therapy manufacturing, leading to the production of more potent and sustainable cellular therapies.